Aspectos de la Biología Reproductiva del Zorzal Chiguanco (Turdus Chiguanco) en el Chaco Serrano de Córdoba, Argentina - Vergara Tabares, David Lautaro (2013)
Some parameters of the breeding biology of the Chiguanco Thrush (Turdus chiguanco) are described in Chaco Serrano forest of Córdoba, Argentina. Searching and monitoring of the Chiguanco Thrush nests were performed between October 2010 and February 2011. We monitored 35 nests of this species. Seven species of trees and bushes, two of them exotics, were used for nesting, mainly at medium height of the plant. Clutch size ranged between two to three eggs; only two nests were parasitized by the Shiny Cowbird (Molothrus bonariensis). The incubation period was 11–12 days long and nestlings hatched asynchronously in clutches of three eggs. Only 10% of nests were successful. From the unsuccessful nests, 97% were predated. The daily rate of nest predation was 0.86 ± 0.02. Only females were responsible for incubation. Females incubated intermittently for periods of 16:24 ± 3:16 min, and took recess bouts of 13:11 ± 2:20 min